The efficiency of public insurance supervision vs. Pareto efficiency - Kurek, Robert (Copernican Journal of Finance & Accounting, 2014)
The objective of the paper is to research whether Pareto optimality can determine the efficiency of activities carried out by public supervision authorities by analyzing literature references and applying the method of verbal description. Having made certain assumptions, Pareto criterion can determine the model reference point in which supervision authorities’ decisions are aimed at improving the situation of consumers without resulting in the simultaneous deterioration of insurance institutions situation. It also ensures proper functioning of the entire market. However, the public aspect of the problem determines the fact that supervision authorities should not search for the model Pareto optimum, but rather focus their activities on obtaining one of many possible optimums responsible for different share of particular entities in the achieved results.